Political liberalism vs. right-wing libertarianism - Ramet, Sabrina P. (Teorija in praksa, 2024)
Among twentieth-century political philosophers, Americans John Rawls and Robert Nozick are generally recognized as giants – both for the boldness of their arguments and for the influence they have exerted. They sketched rival visions. Rawls, inspired by Immanuel Kant, argued for a world characterized by tolerance, equality, and justice as fairness. Nozick, claiming a Lockean heritage but actually inspired by Adam Smith (the “invisible hand”) and Herbert Spencer (“survival of the fittest”), outlined a program for a minimal state, with very little taxation, offering no cushion at all against poverty, and providing no state assistance for the poor, the sick, the disabled, or the widowed. Rawls’ vision is clearly part of the liberal tradition, while Nozick’s championing of a minimal state contains illiberal elements
Keywords: davki; enakost; equality; justice; Libertarizem; Nozick, Robert; political liberalism; politični liberalizem; pravičnost; Rawls, John; taxation